Narratives of the rites and laws of the Yncas - Molina, Cristóbal de 16th cent.; Santa Cruz Pachacuti Yamqui Salcamayhua, Juan de; Avila, Francisco de ca.; Polo de Ondegardo d.; Markham, Clements R. (Works issued by the Hakluyt Society, 1873)
An account of the fables and rites of the Yncas / by C. de Molina -- An account of the antiquities of Peru / by J. de Santa Cruz Pachacuti-Yamqui Salcamayhua -- A narrative of the errors, false gods, and other superstitions and diabolical rites in which the Indians of the province of Huarochiri lived in ancient times / by F. de Avila -- Report by Polo de Ondegardo.